Conceptual foundations of the competitiveness of industrial companies of the Republic of Kazakhstan with the help of a system for implementing ESG principles - Omarova, A.T.; Uspanova, M.V.; Kurmanalina, A.K.; Srailova, G.N.; Orynbassarova, Ye.D. (BUKETOV BUSINESS REVIEW, 2023)
Object: In modern conditions, the most difficult task for companies is to quickly respond to changes and take appropriate measures in the organization and application of financial instruments based on monitoring and evaluating industrial companies in order to compete with the economy. Compliance with the principles of ESG is becoming one of the prerequisites for companies operating in global markets, and a necessary condition for maintaining their competitiveness, since compliance with the principles of ESG has a direct impact on their image as a responsible environmentally and socially oriented company. The purpose of the study is to analyze the competitiveness of industrial companies in the Republic of Kazakhstan with the help of a system for implementing ESG principles, identifying problems and solutions. Methods: The author used methods of scientific knowledge: analysis, synthesis, deduction, induction, abstraction and concretization, generalization and grouping of statistical information, abstract-logical, functional and comparative analyses, interdisciplinary approach. Findings: The author analyzes current trends and ongoing macroeconomic conditions for the functioning of industries in order to improve the processes and mechanisms of strategic management, formulates conclusions and recommendations for the further development and implementation of the ESG approach as a tool with which companies can navigate in the conditions of economic and political turbulence in the market. Conclusions: As a result of the study, it was revealed that, taking into account current trends and the ongoing macroeconomic conditions for the functioning of industries, it is necessary to expediency improve the processes and management mechanisms in compliance with the principles of ESG. In the context of integration processes and the development of financial instruments, modern enterprises have to work in a difficult situation created by market uncertainty and the high dynamics of the economic environment. In this context, companies face difficult tasks, on the one hand, to respond flexibly and quickly to market fluctuations, and on the other hand, to form the necessary financial instruments to improve operational efficiency and sustainable development.